The Impact of Genetic Variants in IL-10 and IL-12p40 on the Susceptibility to Non Hodgkin Lymphoma - Ali, Mayasa Abdulla; Naif, Hassan M; Al-Mayah, Qasim Sharhan (Diyala Journal of Medicine, 2019)
Background: Non-Hodgkin lymphomas (NHLs) are a diverse group of mature lymphoid neoplasms with a wide range of cellular and histological presentations. Numerous environmental and genetic factors affect the incidence of these neoplasms; however the exact causes are beyond the current knowledge. Objective: to investigate the association of genetic polymorphisms in two single nucleotide polymorphisms, which are IL-10-1082A/G and IL-12p401188A/ C, with the incidence NHLs among Iraqi patients. Materials and Methods: Whole blood samples were collected from 55 confirmed patients with NHLs and from 40 family-unrelated, age-matched apparently healthy individuals to represent the control group. DNA was extracted from blood samples and allele specific polymerase chain reaction (AS-PCR) technique was used for genotyping of the two SNPs using specific primers. Results: The SNP IL-10-1082A/G appeared in three genotypes: AA, AG and GG which represented 36.36%, 45.45% and 18.18%% respectively in NHL patients compared to 32.5%, 35% and 32.5%% respectively with insignificant neither between genotypes nor alleles. Similarly, the SNP IL-12p401188A/C had three genotypes which were AA, AC and CC. These genotypes represented 32.73%, 38.18% and 29.09% respectively among NHL patients and 52.5%, 37.5% and 10% respectively among controls with significant difference for the homozygous mutant genotype (OR=4.667, 95%CI=1.319-16.512, P=0.017). Conclusion: IL-10-1082A/G polymorphism has no effect on the incidence of NHLs, while allele C of the SNP IL-12p401188A/C could be considered as a risk factor for these neoplasms.